Aboutness em análise documental de textos literários infantojuvenis: perspectivas para o aprimoramento da representação de conteúdo - Vesú Alves, Roberta Caroline [UNESP]; Ernesto De Moraes, João Batista [UNESP] (My University, 2016)
The content representation of infant-juvenile fictional narrative text, for recovery purposes by potential users, demanded study of Documentary Content Analysis, develop procedures for abstracts elaboration. The goal was to develop procedures of infant-juvenile fictional narrative text abstracts, in Documentary Content Analysis for representation of their structural, thematic, aboutness and characteristic aspects, understood through the Generative Sense Course, Greimasian Semiotic and Theory of Narrative. Exploratory study methodology which allowed analysis of different theories, and procedures for abstracts elaboration were applied in selected text. Representation in abstracts of these texts contains aspects of adapted macrostructure and superstructure, consisting of themes, character, space, story time, type narrator, narrative time and types of literary genres. Application of procedures for elaboration of abstracts in the sample considered the Brazilian infant-juvenile fictional narrative text. Procedures for representation in abstracts considered theoretical basis, respecting the structure and aboutness following the text.
Aboutness in documentary analysis of infant and juvenile literary text perspectives for improving the representation of content
Keywords: Aboutness; Abstract; Documentary Content Analysis; Generative Sense Course; Infant-juvenile fictional narrative text; Theory of narrative